New Insights into the Generation of CD4 Memory May Shape Future Vaccine Strategies for Influenza - Devarajan, Priyadharshini; Bautista, Bianca; Vong, Allen M.; McKinstry, Karl Kai; Strutt, Tara M.; Swain, Susan L. (Frontiers in Immunology, 2016)
Influenza viral evolution presents a formidable challenge to vaccination due to the virus’ ability to rapidly mutate to evade immune responses. Live influenza infections generate large and diverse CD4 effector T cell responses that yield highly protective, long-lasting CD4 T cell memory that can target conserved viral epitopes. We review advances in our understanding of mechanisms involved in generating CD4 T cell responses against the influenza A virus (IAV), focusing on specialized follicular helper (TFH) and CD4 cytotoxic (ThCTL) effector subsets and on CD4 T cell memory. We also discuss two recent findings in context of enhancing vaccine responses. First, that helper T cells require priming with APC secreting high levels of IL-6. Second, that the transition of IAV-generated effectors to memory depends on IL-2, co-stimulation and antigen signals, just before effectors reach peak numbers, defined as the “memory checkpoint”. The need for these signals during the checkpoint could explain why many current influenza vaccines are poorly effective and elicit poor cellular immunity. We suggest that CD4 memory generation can be enhanced by re-vaccinating at this time. Our best hope lies in a universal vaccine that will not need to be formulated yearly against seasonal antigenically-novel influenza strains and will also be protective against a pandemic strain. We suggest a vaccine approach that elicits a powerful T cell response, by initially inducing high levels of APC activation and later providing antigen at the memory checkpoint, may take us a step closer to such a universal influenza vaccine.